Some New Results on Global Dominating Sets. (5th November 2012) - Vaidya, S. K.; Pandit, R. M.
Abstract : A dominating set is called a global dominating set if it is a dominating set of a graph G and its complement G ¯ . A natural question arises: are there any graphs for which it is possible to relate the domination number and the global domination number? We have found an affirmative answer to this question and obtained some graphs having such characteristic.